Invasion Potentials, Spreading Nature and Management Techniques of Sphagneticola Trilobata at University of Chittagong, Bangladesh - Al-Amin, Mohammed; Jannat, Riyajun (Indian Forester, 2022)
Sphagneticola trilobata is a creeping herb species of composite nature. The study was designed to evaluate the invasion potentials due to several factors to visualize the spreading nature with a view to quantifying the responses of different management techniques of the Sphagneticola trilobata at University of Chittagong. The task is followed in experimental design method in field condition and randomized block design is done in several phages of the experiments. The overall results show that Sphagneticola trilobata is an invasive species in the study area and it is spreading fast in newer spots. The rate of horizontal length and regeneration capacity of the species was capable to cover the whole area within 1.51 years through faster sprouting within 4 to 32 days against different control measures applied in the experimental blocks in sites. The area covered by the species at University of Chittagong related linearly with soil pH, plant growth and soil moisture in linear regression model. The study recommended using the plant more in medicine production rather than controlling. This species is of invasive nature but proper utilization was considered as economic and autocontrolling system for Sphagneticola trilobata.